Study on Triggering Characteristics of High Current Triggered Vacuum Switches - Dai Ling, Dai Ling; Han Yongxia, Han Yongxia; Lin Fuchang, Lin Fuchang; Li Hua, Li Hua; Wang Lei, Wang Lei; Zeng Han, Zeng Han; He Zhenghao, He Zhenghao (IEEE transactions on magnetics, 2009)
High current switch is a key component of a pulsed power source. Triggered vacuum switch (TVS) possesses many advantages including wide range of operating voltage, compact structure, low cost and so on, so it is considered as one of the most compelling switch in pulsed power system. This paper describes two types (A and B) of TVS samples with different main electrodes and triggering electrodes. Based on theoretical analysis and experimental results, the triggering characteristics of TVS samples have been researched. The triggering polarity, triggering energy and operating voltage influence the triggering delay and the jitter of delay. To recover the failure of TVS samples caused by decreased triggering energy, series air gap was tried. In the lifetime test, the resistance between the triggering electrodes dropped gradually, leading to the failure of TVS. Both types of TVS have discharges number of 100 shots with 70 kA peak current. The ablation on the main electrodes of type B TVS was slighter than that of type A.